Seasonal Oscillations of daily mean Maximum Temperature in India and neighbourhood - BANERJEE, A. K.; SHARMA, K. K. (MAUSAM, 1966)
The mean daily maximum temperatures of 124 selected observatories have been subjected to harmonic analysis, The annual oscillations are observed to predominate over the other harmonic oscillations. The amplitudes of annual oscillation are highest in northwest of India and least over the west coast, Half-yearly oscillation amplitudes are highest over central India more towards northern latitudes, The close proximity of the dates of onset of SW monsoon and amplitude maxima of the annual oscillations over a major part in northwest India and adjoining area is striking. The regression coefficients of the first and second harmonic amplitude with latitude, longitude and elevation have been worked out and discussed.